The Level of People's Salt Business Empowerment (PUGAR) Reviewed From Market Demand - Sadiqin, Amin; Sunarti, Sunarti (Journal of International Accounting, Taxation and Information Systems, 2024)
The implementation of the People's Salt Business Empowerment Program (PUGAR (Pemberdayaan Usaha Garam Rakyat)) to intensify salt fields and boost people's salt productivity is considered slow. The PUGAR needs to be revitalized to enhance the welfare of salt farmers and achieve industrial salt self-sufficiency by 2015. The aim of this research is to analyze the empowerment of people's salt businesses (PUGAR) based on the aspects of Central Java's industrial salt demand, with a focus on determining the level of empowerment of salt businesses in the Central Java region. The research was conducted by distributing questionnaires to salt farmers and utilizing existing data. The results indicated low market demand but high social and cultural aspects and business sustainability. Short-term priority actions include optimizing applied technology for the production process, improving the distribution chain, and ensuring sustainable market information to stabilize the people's salt business.